LENGTH AND WIDTH OF CRACK GROWTH IN CONCRETE ELEMENT AT CYCLIC LOADING - S. N. Leonovich; K. A. Piradov (Наука и техника)
The paper presents algorithms for calculation of crack length and its width opening under cyclic loading on the concrete of the given composition.A critic ratio of stress intensity and rate of concrete vibro-creeping are used for calculations in addition to conventional strength and deformation characteristics. The analysis shows that rather good correspondence is observed between experimental data and calculative results.